In defence of the common good - Barber, NW (Oxford University Press, 2024)
Vermeule argues that law should uphold community morality, and critiques originalists and progressivists for losing sight of this. Though his critique is powerful, the book shares those problems Vermeule diagnoses in the work of others. As with the originalists, Vermeule’s theory of interpretation is not yet able to provide guidance. We need to know more about its content and its moral base to evaluate its attractions. Additionally, Vermeule underplays strong similarities between progressivists and his own scholarship. Acknowledging these similarities draws attention to a pair of shared institutional problems. First, the moral cost in taking decisions away from individuals and passing them to state institutions: using law to regulate an issue runs the risk of error, and may produce morally significant side-effects by coercively limiting people’s options. Secondly, morality speaks to the institutional process by which decisions are produced as well as their substance: the way we decide is important.